Myeloid Diagnostic and Prognostic Markers of Immune Suppression in the Blood of Glioma Patients - Del Bianco, Paola; Pinton, Laura; Magri, Sara; Canè, Stefania; Masetto, Elena; Basso, Daniela; Padovan, Marta; Volpin, Francesco; d’Avella, Domenico; Lombardi, Giuseppe; Zagonel, Vittorina; Bronte, Vincenzo; et al. (Frontiers in Immunology, 2022)
Background Although gliomas are confined to the central nervous system, their negative influence over the immune system extends to peripheral circulation. The immune suppression exerted by myeloid cells can affect both response to therapy and disease outcome. We analyzed the expansion of several myeloid parameters in the blood of low- and high-grade gliomas and assessed their relevance as biomarkers of disease and clinical outcome. Methods Peripheral blood was obtained from 134 low- and high-grade glioma patients. CD14+, CD14+/p-STAT3+, CD14+/PD-L1+, CD15+ cells and four myeloid-derived suppressor cell (MDSC) subsets, were evaluated by flow cytometry. Arginase-1 (ARG1) quantity and activity was determined in the plasma. Multivariable logistic regression model was used to obtain a diagnostic score to discriminate glioma patients from healthy controls and between each glioma grade. A glioblastoma prognostic model was determined by multiple Cox regression using clinical and myeloid parameters. Results Changes in myeloid parameters associated with immune suppression allowed to define a diagnostic score calculating the risk of being a glioma patient. The same parameters, together with age, permit to calculate the risk score in differentiating each glioma grade. A prognostic model for glioblastoma patients stemmed out from a Cox multiple analysis, highlighting the role of MDSC, p-STAT3, and ARG1 activity together with clinical parameters in predicting patient’s outcome. Conclusions This work emphasizes the role of systemic immune suppression carried out by myeloid cells in gliomas. The identification of biomarkers associated with immune landscape, diagnosis, and outcome of glioblastoma patients lays the ground for their clinical use.